Holocene climatic change in Morocco: a quantitative reconstruction from pollen data - Cheddadi, R.; Lamb, H. F.; Guiot, J.; van der Kaars, S. (Climate Dynamics, 1998)
Annual precipitation, July and January tem- peratures were reconstructed from a continuous Holo- cene pollen sequence from the Middle Atlas, Morocco, using the best modern analogues method. The recon- structions show a clear difference between the early and late Holocene: from &10 ka to &6.5 ka the climate was drier and warmer than during the period since 6.5 ka. The average value of annual precipitation was &870mm until 6.5 ka, then rose to &940 mm. Be- tween 10 ka and 6.5 ka January and July temperatures were about 4 °C higher than the present. Both temper- atures show a marked decrease between 7 ka and 6 ka. After 6.5 ka July and January temperatures fluctuated between 21 and 23 °C, and 2.5 and 5 °C respectively. January temperatures show a period of intermediate values (&3.5 °C) between 4 ka and 5.5 ka. The recon- structed climate values generally match palaeolim- nological data from the same core, which show five intervals of low lake level during the Holocene. They are also consistent with regional-scale COHMAP simulated palaeoclimate that shows contrasting pat- terns of rainfall variation between the northwester- nmost part of Africa and the intertropical band
APSAPS
Keywords: climate; Holocene; Morocco; paleoclimate; pollen